Bismuth oxyhalide layered materials for energy and environmental applications. (November 2017) - Di, Jun; Xia, Jiexiang; Li, Huaming; Guo, Shaojun; Dai, Sheng
Abstract: Photocatalytic solar energy conversion is considered one of the most promising pathways to address the global energy shortage and environmental crisis. Layered bismuth oxyhalides are a new class of photocatalytic materials with a strong light response to boost solar energy conversion due to their appealing energy band structure and unique layered structure. This critical review summarizes recent progress in designing and tuning new bismuth oxyhalide materials to boost solar energy conversion. We start with methods to prepare and tune bismuth oxyhalides to enhance photocatalysis: structural engineering via control of the bismuth-rich state, elemental doping, defect control, interface engineering, solid solutions, inner coupling, and heterojunction construction. Then advancements in versatile photocatalytic applications of bismuth oxyhalide–based photocatalysts in the areas of oxygen evolution, hydrogen evolution, CO2 reduction, nitrogen fixation, organic syntheses, disinfection, and pollutant removal are discussed. Finally, the major challenges and opportunities regarding the future exploration of bismuth oxyhalide–based materials in photocatalysis are presented. The present review will deepen understanding regarding bismuth oxyhalides and open new directions in designing and optimizing advanced bismuth oxyhalide–based materials for energy and environmental applications. Graphical abstract: Highlights: Various strategies for synthesis and performance improvement of layered bismuth oxyhalides materials have been surveyed. The application of photocatalytic layered bismuth oxyhalides materials in energy and environment has been proposed. Insight the structure-activity relationship from light harvesting, interfacial reactions and charge separation.